An adaptive fuel cell hybrid vehicle propulsion sizing model - Di Yang, J; Shearing, PR; Millichamp, J; Suter, T; Brett, DJL; Robinson, JB (IEEE, 2024)
As we enter the age of electrochemical propulsion, there is an increasing tendency to discuss the viability or otherwise of different electrochemical propulsion systems in zero-sum terms. These discussions are often grounded in a specific use case; however, given the need to electrify the wider transport sector it is evident that we must consider systems in a holistic fashion. When designed adequately, the hybridisation of power sources within automotive applications has been demonstrated to positively impact fuel cell efficiency, durability, and cost, while having potential benefits for the safety of vehicles. In this paper, the impact of the fuel cell to battery hybridisation degree is explored through the key design parameter of system mass. Different fuel cell electric hybrid vehicle (FCHEV) scenarios of various hydridisation degrees, including light-duty vehicles (LDVs), Class 8 heavy goods vehicles (HGVs), and buses are modelled to enable the appropriate sizing of the proton exchange membrane (PEMFC) stack and lithiumion battery (LiB) pack and additional balance of plant. The operating conditions of the modelled PEMFC stack and battery pack are then varied under a range of relevant drive cycles to identify the relative performance of the systems. By extending the model further and incorporating a feedback loop, we are able to remove the need to include estimated vehicle masses a priori enabling improving the speed and accuracy of the model as an analysis tool for vehicle mass and performance estimation.